2020
DOI: 10.1155/2020/3584105
|View full text |Cite
|
Sign up to set email alerts
|

Boundedness of Fractional Integral Operators Containing Mittag-Leffler Function via Exponentially s-Convex Functions

Abstract: The main objective of this paper is to obtain the fractional integral operator inequalities which provide bounds of the sum of these operators at an arbitrary point. These inequalities are derived for s-exponentially convex functions. Furthermore, a Hadamard inequality is obtained for fractional integrals by using exponentially symmetric functions. The results of this paper contain several such consequences for known fractional integrals and functions which are convex, exponentially convex, and s-convex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…ese estimates have a wider range of applications. Here, we shall propose some new estimates of the remainder term E(ϱ, d) which supplement, in a sense, those established in [30,[32][33][34][35].…”
Section: Some Applications Of Caputo-fabrizio Fractional Integral Inequalities To the Trapezoidal Formulamentioning
confidence: 75%
See 1 more Smart Citation
“…ese estimates have a wider range of applications. Here, we shall propose some new estimates of the remainder term E(ϱ, d) which supplement, in a sense, those established in [30,[32][33][34][35].…”
Section: Some Applications Of Caputo-fabrizio Fractional Integral Inequalities To the Trapezoidal Formulamentioning
confidence: 75%
“…It is clear that if the mapping f is not twice differentiable or the second derivative is not bounded on (a, b), then (49) cannot be applied. In recent studies [30,[32][33][34][35], Dragomir and Wang showed that the remainder term E(ϱ, d) can be estimated in terms of the first derivative only. ese estimates have a wider range of applications.…”
Section: Some Applications Of Caputo-fabrizio Fractional Integral Inequalities To the Trapezoidal Formulamentioning
confidence: 99%
“…Our conclusions are applicable, since the expected value of a random variable is consistently bounded above by the expected value of the convex function of that random variable. It will be interesting to find parallel results by using the proposed definition in this study in the setting of other fractional integrals [14,15].…”
Section: Fractional Integral Inequalitiesmentioning
confidence: 94%
“…Corollary 8. If we consider α = 1 and λ = 0 in (12), then the following inequality holds for m-convex functions: Lemma 10 (see [24]). Let f : ½a, b → ℝ be strongly ðα, mÞ -convex function, 0 < a < mb .…”
Section: Journal Of Function Spacesmentioning
confidence: 99%
“…The objective of this paper is to obtain bounds of unified integral operators using strongly ðα, mÞ-convexity. It is defined as follows [24].…”
Section: Introductionmentioning
confidence: 99%